RESOLVA AS EQUAÇÕES ABAIXO
X²-6X+9=0
9X²-12X+4=0
Soluções para a tarefa
Respondido por
2
x² - 6x + 9 = 0
Δ = b² - 4 · a · c
Δ = (-6)² - 4 · 1 · 9
Δ = 36 - 36 = 0
x = (- b +- √Δ)/ 2 · a
x = (6 +- √0)/ 2
x = 6/2
x = 3
9x² - 12x + 4 = 0
Δ = (-12)² - 4 · 9 · 4
Δ = 144 - 144 = 0
x = (12 +- √0)/ 2 · 9
x = 12/18
x = 2/3
Δ = b² - 4 · a · c
Δ = (-6)² - 4 · 1 · 9
Δ = 36 - 36 = 0
x = (- b +- √Δ)/ 2 · a
x = (6 +- √0)/ 2
x = 6/2
x = 3
9x² - 12x + 4 = 0
Δ = (-12)² - 4 · 9 · 4
Δ = 144 - 144 = 0
x = (12 +- √0)/ 2 · 9
x = 12/18
x = 2/3
Respondido por
0
Resposta:iae
Explicação passo-a-passo:eee
Perguntas interessantes
Matemática,
1 ano atrás
Administração,
1 ano atrás
Geografia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás